THE SIGNIFICANCE OF COMMUNICATION MODELS AND TEACHING STYLES IN COLLABORATIVE LEARNING: A CASE STUDY OF THE ITALIAN LANGUAGE - Šuvaković, Aleksandra B.; Govedarica, Jovana Ž. (Metodička teorija i praksa, 2025)
Managing a foreign language classroom represents a complex process that requires teachers to possess a wide range of skills and abilities. The effective implementation of classroom management strategies has proven crucial in overcoming challenges arising from heterogeneous monolingual classrooms. Examining key aspects such as management style, communication models, language input, and cooperative learning highlights the importance of a comprehensive approach. The democratic/integrative management style, with a focus on communicative and humanistic-affective approaches, plays a crucial role in meeting the needs of students. Asymmetric interaction in communication often emerges in institutional contexts, where the teacher’s role is dominant. The quality of communication models in the classroom directly depends on fulfilling the first aspect. Language input in the classroom, tailored to the group’s needs, aims at developing language competence in line with educational objectives. Cooperative learning creates space for a better understanding of others’ needs, reflection on one’s identity in the classroom, and the acquisition of intercultural competence. All the mentioned dimensions of managing a foreign language classroom are interconnected and require careful integration into the teaching process to achieve effective learning and meet the needs of all participants in the classroom. This underscores the importance of continuous teacher development towards a comprehensive approach to managing a foreign language classroom. Keywords: Classroom management of foreign languages, teacher-facilitator, students, classroom management styles and communication models, collaborative learning.